Prediction of the anticlastic shape changes of hybrid composite material - Baikovs, Andris; Rocēns, Kārlis (Journal of Civil Engineering and Management, 2010)
In search of structurally better and aesthetically more attractive solutions of the erection of various structures, non‐standard anticlastic elements are used more frequently. Therefore preservation of the initial shape of timber composite material sheets by using of reinforced plastic reinforcement has been investigated. Calculation model for determination of the thickness of rational reinforcement anticlastic sheet, which provides change of the original bending radius under variable moisture conditions (Baikovs and Rocens, 2006) within the limits of preferable intervals is developed by authors and using finite element method, calculations and modelling of sheet deformations are carried out with software package ANSYS v.11 (henceforth FEM) and by developed analytical method. Comparative research of the results calculated with the FEM and developed calculation model showed that the difference between results in the three cases investigated, when the composite timber material is reinforced on the top, bottom and both sides for the most of the cases does not exceed 3.3%. An opportunity to provide the original shape of anticlastic timber composite material sheets by using glass fibre reinforced plastic reinforcement under variable moisture conditions and not exceeding the difference of 5% has been demonstrated. First Published Online: 24 Jun 2011